Volúmen prostático y su relación con la severidad de síntomas en pacientes con hiperplasia benigna de próstata - Inca Ocas, Romy Laura (2002)
The present prospective, descriptive-correlational study evaluated 75 patients with a clinical diagnosis of BPH who attended the outpatient clinic of the Urology Service of the Belén de Trujillo Hospital between June-August of 2002, to whom the International Questionnaire was applied. IPSS and they underwent a transabdominal ultrasound examination, with the purpose of determining the average prostate volume, the severity of the symptoms, the relationship between prostate volume and severity of symptoms and estimating the correlation coefficient between the prostate volume and the symptom score. . The average age, prostate volume and symptom score of the patients was 67.13 ± 8.32 years, 58.02 ± 28.08 ce and 16.20 ± 8.17, respectively. Frequency (3.23 ± 2.02) was the symptom that had the highest average score; the urgency being the symptom with the lowest average (1.52 ± 1.41). The most frequent symptom was nocturia (96%) and the least frequent was the interruption of the voiding stream (56%). Of the total patients, 32 (42.67%) were severely symptomatic, 27 (36%) were moderately symptomatic and 16 (21.33%) were mildly symptomatic. The middle lobe was present in 14.67% of the patients. There was no statistically significant difference in the average prostate volumes between the groups of patients with different level of symptom severity (F = 0.86, p> 0.05). No correlation was found between prostatic volume and symptom score (r = 0.124, p> 0.05). It is concluded that : 1.- The average prostatic volume in patients with benign prostatic hyperplasia is 58 ± 28.08 ce. 2.- In patients with benign prostatic hyperplasia, severe symptoms are the most frequent. 3 .- There is no significant difference in prostate volume according to the level of severity of symptoms in patients with benign prostatic hyperplasia. 4.- The prostatic volume in patients with benign prostatic hyperplasia does not correlate with the symptom score